Gender and Play : How Indonesian Street Children - Fadilah, Farah Nur; Qosyasih, Nelis Nazziatus Sadiah (Jurnal Ilmiah POTENSIA, 2025)
Street children are often constructed as weak individuals who miss out on a pleasant childhood because they have to work and do not have the same opportunities as most of their peers. In addition, street children are often considered to have insufficient understanding of science or gender issues due to their limited access to knowledge and experience. Using a post-developmentalism approach, this article seeks to go beyond the existing idea of ​​play by exploring how street children in Jakarta, Indonesia. The urgency of this study is to try to dismantle the perceptions that have been understood by the community regarding street children regarding the concept of gender and negotiating play with work as part of their daily lives. So this study is important to provide attention and in-depth understanding that street children have the same and equal opportunities. The author took a qualitative approach to collect data on 7 street children and their guardians, mainly through observation and ongoing conversations. The results of this study found four findings, namely street children's interpretations of boys and girls, children's tendencies towards play, color preferences and social influences of street children, and perceptions of professions and gender. The conclusion is that street children have the same frequency regarding the meaning of gender in their daily activities, such as understanding the differences between women and men, understanding color choices and how street children view professions.